2019
DOI: 10.1186/s12866-019-1459-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community of methanogens in the large intestine of finishing pigs

Abstract: Background Methane emissions from pigs account for 10% of total methane production from livestock in China. Methane emissions not only contribute to global warming, as it has 25 times the global warming potential (GWP) of CO 2 , but also represent approximately 0.1~3.3% of digestive energy loss. Methanogens also play an important role in maintaining the balance of the gut microbiome. The large intestines are the main habitat for the microbiome in pigs. Thus, to better un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…In addition, a study by Kim et al found that the Prevotellaceae family is predominant at ten weeks of age [ 50 ], which was also observed in our study. Moreover, the temporal pattern of the composition and relative abundance of archaeal taxa is comparable with data from multiple studies [ 49 , 53 ].…”
Section: Discussionsupporting
confidence: 75%
“…In addition, a study by Kim et al found that the Prevotellaceae family is predominant at ten weeks of age [ 50 ], which was also observed in our study. Moreover, the temporal pattern of the composition and relative abundance of archaeal taxa is comparable with data from multiple studies [ 49 , 53 ].…”
Section: Discussionsupporting
confidence: 75%
“…The archaeal composition based on metagenomics was different from that revealed by 16s rRNA or mcrA genes. Mi and colleagues found that the genus Methanobrevibacter was the dominant archaeal taxon with an average relative abundance of 57% in the large intestine of nishing pigs [19]. Furthermore, Methanobrevibacter was also reported as the overwhelmingly dominant archaeal genus and accounted for 95.01-100% of all archaeal reads in pigs in other studies [17,18].…”
Section: Discussionmentioning
confidence: 97%
“…The archaeal composition based on metagenomics was different from that revealed by 16s rRNA or mcrA genes. Mi and colleagues found that the genus Methanobrevibacter was the dominant archaeal taxon with an average relative abundance of 57% in the large intestine of finishing pigs [19]. Furthermore, Methanobrevibacter was also reported as the overwhelmingly dominant archaeal genus and accounted for 95.01%-100% of all archaeal reads in pigs in other studies [17,18].…”
Section: Discussionmentioning
confidence: 97%